An improved model analysis approach for hybrid thermo-piezoelectric micro actuator with thermo-piezoelectric coupling. (March 2019) - Chen, Ning; Yan, Peng; Ouyang, Jun
Highlights: An improved model for bending of hybrid thermo-PZT micro actuators. Electro-thermal coupling effect on the thermal expansion coefficient. Guidelines for geometry optimization of hybrid thermo-PZT micro actuators. Successful demonstration on simulations and experiments. Abstract: This paper presents a new modeling and analysis approach for the bending characteristics of hybrid thermo-piezoelectric micro actuators by considering the effect of thermo-piezoelectric coupling, which helps to better capture the bending behavior of piezoelectric beams in various smart sensor or actuator applications. In particular, we investigate the temperature induced change on the piezoelectric coefficient, as well as the electric field and piezoelectric coefficient changes on the thermal expansion coefficient where the bending characteristics of thermo-piezoelectric micro actuators are further obtained subjected to the electric and temperature fields, under the thermo-piezoelectric coupling condition. The analysis of thickness ratio and curvature provides a guidance for geometry optimized of the thermo-piezoelectric micro actuator based on the design requirements. To verify the effectiveness of the proposed approach, simulations and experiments are also conducted for a thermo-piezoelectric micro actuator (PZT-5A) under various thermal and electric loads, where theoretical values agree well with experiments, outperforming existing results.